EFFECTIVE METHODS OF USING NEW TECHNOLOGIES IN FOOTBALL TEACHING - Khushmurodov , Bekzod Abduraimovich (Innovative Development in Educational Activities, 2023)
Effective ways of introducing new technologies in football teaching in order to increase the intensity of training are discussed.